Three New Quinazoline-Containing Indole Alkaloids From the Marine-Derived Fungus Aspergillus sp. HNMF114 - Liu, Sha-Sha; Yang, Li; Kong, Fan-Dong; Zhao, Jia-Hui; Yao, Li; Yuchi, Zhi-Guang; Ma, Qing-Yun; Xie, Qing-Yi; Zhou, Li-Man; Guo, Meng-Fei; Dai, Hao-Fu; Zhao, You-Xing; et al. (Frontiers in Microbiology, 2021)
By feeding tryptophan to the marine-derived fungus Aspergillus sp. HNMF114 from the bivalve mollusk Sanguinolaria chinensis, three new quinazoline-containing indole alkaloids named aspertoryadins H-J (1-3), along with 16 known ones (4-19), were obtained. The structures of the new compounds were elucidated by the analysis of spectroscopic data combined with quantum chemical calculations of NMR chemical shifts and ECD spectra. Structurally, compound 3 represent the first example of this type of compounds bearing an amide group at C-3. Compounds 10 and 16 showed potent α-glycosidase inhibitory activity with IC50 values of 7.18 and 5.29 μM, and compounds 13 and 14 showed clear activation effect against ryanodine receptor from Spodoptera frugiperda (sfRyR), which reduced the [Ca2+]ER by 37.1% and 36.2%, respectively.